2002
DOI: 10.1046/j.1525-139x.2002.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Peritoneal Dialysis Symposium: APD Prescription: Achieving the Adequacy Goals

Abstract: In the last few years, automated peritoneal dialysis (APD) has undergone considerable improvements due to technological developments. The definition of a minimal dose of peritoneal dialysis (PD) has not yet been completely assessed. Appropriate use of APD requires an evaluation of dialytic efficiency in terms of dialytic indexes and their targets. Many dialytic treatment modalities have been performed in order to achieve adequacy targets. Some aspects have to be taken into consideration to reach the optimal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The keyword with the strongest citation strength was “adequacy” (9.91), and it lasted for the initial years (2000–2004). An article summarized some possible means to achieve the desired adequacy targets, including establishing individual APD prescriptions and using PD techniques 43 . The keyword “outcome” was the second strongest word (6.14) and also has the longest duration for 10 consecutive years since 2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The keyword with the strongest citation strength was “adequacy” (9.91), and it lasted for the initial years (2000–2004). An article summarized some possible means to achieve the desired adequacy targets, including establishing individual APD prescriptions and using PD techniques 43 . The keyword “outcome” was the second strongest word (6.14) and also has the longest duration for 10 consecutive years since 2010.…”
Section: Resultsmentioning
confidence: 99%
“…An article summarized some possible means to achieve the desired adequacy targets, including establishing individual APD prescriptions and using PD techniques. 43 The keyword "outcome" was the second strongest word (6.14) and also has the longest duration for 10 consecutive years since 2010. The keywords "technique failure" and "patient survival" are similar to "outcome," which suggested that the prognosis of patients has always been the main topical subject in APD research.…”
Section: Analysis Of Co-occurring Abstract and Burst Detectionmentioning
confidence: 99%
“…18 Although sometimes difficult to obtain, given the associated time burden to patients and clinical staff, 19 results of peritoneal equilibration test should also guide APD prescriptions. 20 Patients exhibiting high solute transport are well suited for shorter dwell times and nocturnal APD, whereas those with low transport generally require longer dwell times. In this analysis, high transporters were treated with more nighttime cycles, shorter dwell times per cycle, and a marked increase in total nighttime treatment volumes.…”
Section: Discussionmentioning
confidence: 99%